PROCESS PRODUCTION OF BIODIESEL USING A MINI PLANT - Pasae, Yoel; Ranak, Medris; Bulo, Lyse; Allo, Eda Lolo; Palulullungan, Liberthin; Petrus (International Journal of Research -GRANTHAALAYAH, 2022)
Biodiesel is a type of alternative fuel to replace diesel. Refined Bleached Deodorized Palm Oil (RBDPO) is a raw material that has the potential to be processed into biodiesel because of its abundant availability and easy to obtain. The focus of this research is to carry out the biodiesel production process using a mini biodiesel plant with a capacity of 50 liters/batch, and the catalyst used is NaOH. The results showed that the portable factory can produce biodiesel with a yield of 90.86%. The characteristics of the biodiesel produced were analyzed and the following values were obtained: density 0.89 g/mL, viscosity 4.69 CSt, acid number 1.68 mg KOH/g, and saponification number 179.52 mg KOH/g.